Arabidopsis IQM4, a Novel Calmodulin-Binding Protein, Is Involved With Seed Dormancy and Germination in Arabidopsis - Zhou, Yu Ping; Wu, Jing Hui; Xiao, Wen Hui; Chen, Wei; Chen, Qiong Hua; Fan, Tian; Xie, Chu Ping; Tian, Chang-En (Frontiers in Plant Science, 2018)
Seed dormancy and germination are regulated by complex mechanisms controlled by diverse hormones and environmental cues. Abscisic acid (ABA) promotes seed dormancy and inhibits seed germination and post-germinationgrowth. Calmodulin (CaM) signals are involved with the inhibition of ABA during seed germination and seedling growth. In this study, we showed that Arabidopsis thaliana IQM4 could bind with calmodulin 5 (CaM5) both in vitro and in vivo, and that the interaction was the Ca2+-independent type. The IQM4 protein was localized in the chloroplast and the IQM4 gene was expressed in most tissues, especially the embryo and germinated seedlings. The T-DNA insertion mutants of IQM4 exhibited the reduced primary seed dormancy and lower ABA levels compared with wild type seeds. Moreover, IQM4 plays key roles in modulating the responses to ABA, salt, and osmotic stress during seed germination and post-germination growth. T-DNA insertion mutants exhibited ABA-insensitive and salt-hypersensitive phenotypes during seed germination and post-germination growth, whereas IQM4-overexpressing lines had ABA- and osmotic-hypersensitive, and salt-insensitive phenotypes. Gene expression analyses showed that mutation of IQM4 inhibited the expression of ABA biosynthetic genes NCED6 and NCED9, and seed maturation regulators LEC1, LEC2, ABI3, and ABI5 during the silique development, as well as promoted the expression of WRKY40 and inhibited that of ABI5 in ABA-regulated seed germination. These observations suggest that IQM4 is a novel Ca2+-independent CaM-binding protein, which is positively involved with seed dormancy and germination in Arabidopsis.